Monocyclic and bicyclic CO4: how stable are they?. Issue 111 (26th October 2015) - He, Fei-fei; Gao, Si-meng; de Petris, Giulia; Rosi, Marzio; Ding, Yi-hong
Abstract : For the first time the barriers for the CO2 -elimination from 1 1 and 1 2 energy-rich CO4 were located, they amount to 28.7 and 14.7 kcal mol −1 at the CASPT2(18e, 12o)/CBS level of theory, and 23.5 and 21.1 kcal mol −1 at the UCCSD(T)/CBS level of theory. Abstract : Seeking promising molecular species with huge energy release and significant kinetic stability continues to be a hot topic and a great challenge in the field of high-energy density materials (HEDMs). CO4 is the first high-order carboxide that has the potential as an energetic molecule. However, the intrinsic kinetic stability of its two most studied energy-rich isomers, i.e., 1 1 (monocyclic) and 1 2 (bicyclic), has remained quite unclear in spite of numerous studies. This has greatly hindered the quantitative stability assessment of 1 1 and 1 2 under various conditions as well as the justification of their prospect as energetic candidates. In this work, for the first time we report the rate-determining transition states associated with the CO2 -elimination from 1 1 and 1 2 . The thermodynamics of 1 1 and 1 2 was described using G3B3, CBS-QB3, G4, W1BD, CCSD(T)/CBS and CASPT2/CBS, while the kinetic stability was analyzed based on broken-symmetry UCCSD(T)/CBS and CASPT2/CBS single-point energy calculations on UB3LYP geometries. The rate-determining barriers for the dissociation of 1 1 and 1 2 into CO2 + 1 O2 at 298 K were found to amount to 28.7 and 14.7 kcal mol −1 at the CASPT2(18e, 12o)/CBS level of theory, and 23.5 and 21.1 kcal mol −1 at the UCCSD(T)/CBS level of theory, respectively. 1 1 is a kinetically stable energetic molecule, which releases 45.2 kcal mol −1 upon dissociation into CO2 + 1 O2 at the CASPT2(18e, 12o)/CBS level and 38.9 kcal mol −1 at the UCCSD(T)/CBS level, and could serve as a rigid energetic building block for larger oxocarbons. The bicyclic 1 2 releases much higher energy, 79.3 kcal mol −1 at the CASPT2(18e, 12o)/CBS level and 73.4 kcal mol −1 at the CASPT2-corrected UCCSD(T)/CBS level whereas the barrier for dissociation is lower than that of monocyclic 1 1 .